Penalaran Ta'lili dalam Hukum Islam: Telaah Corak Penalaran Hukum Islam dalam Upaya Penerapan Maqasid al-Shari'ah - Kutbuddin Aibak (Islamica: Jurnal Studi Keislaman, 2006)
?Ijtih?d is the third legal source of Islam whose object is all things about which the Qur?an and the Sunnah are silent (m? l? na?? ?fih). From the perspective of the U??l al-Fiqh, there have been methods of ijtih?d put forward by the ?Ulama, which include qiy?s, isti?l?h, istish?b and ?urf. These methods in the final analysis, should be based on what is commonly known as maq??id al-shar??ah (human interest) when put into practice. When ijtihad is undertaken furthermore, two modes of thinking are normally born out of maq??id al-shar??ah, one of which being ?and this is the focus of our analysis- the ta?l?l? mode of thinking. The ta?l?l? mode of thinking is about discovering the reasons (?illah) behind certain religious rulings. It comes into existence as a result of the fact that the texts of the Qur?an and the Sunnah always mention the reasons when issuing religious rulings. And this has become the starting point of the mujtahids in resolving various legal issues that they face. They start by discovering first the reasons and then proceed to issue the ruling. As far as the science of U??l al-Fiqh is concerned, qiy?s and istihs?n belong to this ta?l?l? mode of thinking.